Pengaruh Pelatihan Media Digital terhadap Perkembangan Ekonomi dan Dakwah Masyarakat Desa Durian Kecamatan Pantai Labu - Ellyza Cindi Mentari; Gita Islya Asmara; Sudianto Sudianto; Vega Liana; Anggi Mayasari Lubis (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This research was conducted by KKN group of 30 North Sumatra State Islamic University (UINSU) which aims to find out and explain how the influence of digital media training on economic development and da'wah in the Durian Village community. This topic attracted the attention of KKN Group 30 because there were still many facts found in the field related to the literacy of the people of Durian Village to digital media, especially for economic development and da'wah in rural communities. The respondents from this study were all Durian Village communities who took part in digital media training. This study uses quantitative research with survey methods and statistical methods, while the data obtained will be tested using SPSS software. From the results of the research and the data obtained, it can be concluded: 1). There is a positive and significant influence between digital media training and the economic development of rural communities by 91%. 2) There is a positive and significant influence between digital media training and the development of da'wah by 84%. So it can be concluded that after holding digital media training, people are increasingly aware of digital media, especially to develop the economy and da'wah through digital media Keywords: Training, Digital Media, Da'wah, Economy, Society